The Semantics of Repression: Linking, Opposing, and Linking again Rehabilitation and Protection of Society - Piñero, Verónica (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2006)
Having explored the youth criminal legislation enacted by the Canadian federal government from the year 1857 to the year 2005, the author attempts to demonstrate that youth criminal intervention has moved from the notion of "child protection" to the notion of "protection of society." The significance of this theoretical shift is that, while the former sort of intervention is mostly concerned with the notions of "reintegration" and "inclusion", the latter is concerned with the notions of "deterrence" and "exclusion." For this study, the author first analyzes the societal factors that led Canadian parliamentarians to enact the Juvenile Delinquents Act (1908). In addition, she focuses on a specific amendment enacted in the year 1924 that "increased" the number of behaviors to be controlled through criminal law legislation. Second, the author discusses the circumstances that led parliamentarians to enact the Young Offenders Act (1982) and the Youth Criminal Justice Act (2002). Moreover, she examines an amendment enacted in the year 1995 that modified the declaration of principles of the Young Offenders Act by introducing the notion of "crime prevention." Finally, she analyzes a case law released in the year 2003 by the Quebec Court of Appeal, Québec v. Canada. This decision declared the unconstitutionality of some specific sections of Bill C-7 (current Youth Criminal Justice Act) that allow the disclosure of young offenders' private information and reverse the onus probandi for the imposition of adult sentences on young offenders. The position of the author is that, even though those sections can be unconstitutional, they are coherent with current theoretical trends in the area of youth criminal law intervention.